Local regulation of postprandial motor responses in ileal pouches. Issue 4 (1st October 1999) - Mularczyk, A; Contessini-Avesani, E; Cesana, B; Bianchi, P A; Basilisco, G
Abstract : BACKGROUND: Local mechanisms are involved in the postprandial regulation of ileal tone in healthy subjects, but whether these mechanisms affect the postprandial tonic response of ileal pouches has not yet been investigated. AIMS: To study the effect of a meal on pouch tone and phasic motor activity in patients with gut continuity or ileostomy and, in the latter group, the effect of a pouch perfusion with chyme or saline. PATIENTS: Twenty patients with ileal pouches: 10 with gut continuity and 10 with ileostomy. METHODS: Pouch tone and the frequency of phasic volume events were recorded with a barostat under fasting and postprandial conditions and after perfusion of the isolated pouch with chyme or saline. RESULTS: The meal increased pouch tone and the frequency of phasic volume events in the patients with gut continuity, but not in those with ileostomy. Pouch perfusion with chyme induced a greater increase in pouch tone than saline. CONCLUSIONS: The meal stimulated pouch tone and phasic motor activity. These effects were at least partially related to local pouch stimulation by intraluminal contents.